Efek Panoptikon Orde Baru dalam Cerkak Berjudul Seksi Saka Menara Karya Suparto Brata - Fitria, Ajeng Aisyah; Priyatama, Ardian Nugraha (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
The ruling state employs various methods to control its citizens, both through legal institutions and through entities deemed